Advances in Cadaverine Bacterial Production and Its Applications. (June 2017) - Ma, Weichao; Chen, Kequan; Li, Yan; Hao, Ning; Wang, Xin; Ouyang, Pingkai
Abstract: Cadaverine, a natural polyamine with multiple bioactivities that is widely distributed in prokaryotes and eukaryotes, is becoming an important industrial chemical. Cadaverine exhibits broad prospects for various applications, especially as an important monomer for bio-based polyamides. Cadaverine-based polyamide PA 5X has broad application prospects owing to its environmentally friendly characteristics and exceptional performance in water absorption and dimensional stability. In this review, we summarize recent findings on the biosynthesis, metabolism, and physiological function of cadaverine in bacteria, with a focus on the regulatory mechanism of cadaverine synthesis in Escherichia coli ( E. coli ). We also describe recent developments in bacterial production of cadaverine by direct fermentation and whole-cell bioconversion, and recent approaches for the separation and purification of cadaverine. In addition, we present an overview of the application of cadaverine in the synthesis of completely bio-based polyamides. Finally, we provide an outlook and suggest future developments to advance the production of cadaverine from renewable resources.